Effects of Horizontal Wind Structure on a Gravity Wave Event in the Middle Atmosphere Over Syowa (69°S, 40°E), the Antarctic - Kogure, Masaru; Nakamura, Takuji; Ejiri, Mitsumu K.; Nishiyama, Takanori; Tomikawa, Yoshihiro; Tsutsumi, Masaki (Geophysical Research Letters, 2018)
journal article